An Assessment of Cadmium and Zinc in Stream Contaminated by Mining Activities using Aquatic Insects - พรหมมิ ผู้ช่วยศาสตราจารย์ ดร. แตงอ่อน; เดชชัย พิมพ์ชฎา; พยัคฆา อำพล (Journal of Food Health and Bioenvironmental Science, 2016)
Metal accumulation in the sediments results in serious environmental problems to the surrounding areas, affecting water quality and resulting in bioaccumulation of metals by the aquatic organisms. The aim in this study was analyzed the cadmium (Cd) and zinc (Zn) in stream sediments and aquatic insects in five sampling sites (MT1-MT5) at Mae Tao Creek, Mae Sot District, Tak Province in October and December 2011. The concentration of heavy metals in stream sediments and aquatic insects near mining area were higher than area that far from mining area. The physicochemical water quality variable, water temperature, dissolved oxygen, pH, turbidity, nitrate-nitrogen, orthophosphate and ammonia-nitrogen were not significantly related among sampling sites (P>0.05). The concentration of cadmium and zinc in stream sediment was positive significantly related to sulfate (P<0.01, P<0.05). The concentration of cadmium in Hemiptera was negative significantly related to nitrate-nitrogen (P<0.05).